PELATIHAN APLIKASI MS EXCEL UNTUK EFISIENSI PENGELOLAAN DATA SISWA PADA GURU SMPK SETIA BUDI - MALANG - Tri Istining Wardani (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
The purpose of this community service activity is to provide training in the field of science and technology utilizing Microsoft Excel application to help the teachers to improve the quality of teaching and learning services to students in terms of students’ database management. This community service activity was conducted in SMPK Setia Budi, Jatimulyo - Malang through Knowledge Transfer, Discussion, Practising, and Problem Solving. The results that can be achieved from this community service activity were the increasing of utilization of science and technology facility to support teaching and learning process, improving the service quality to the students’ database management, as well as increasing teacher’s work efficiency to the students’ service.